Dakwah Fardiyah Penganten Baru - Nelson Nelson (Jurnal Dakwah dan Komunikasi, 2018)
This article is a study of literature about the formulation of Da'wah fardiyah towards married couples to realize sakinah family. The researcher interests to investigate this case because if it observeded, newmarried couple who have various level of education. According to the researcher assumption that at this time there is new married couple in forming a family like flowing water, where the direction is, anchored still in the shadow. Therefore, the researcher formulates the problems of how to formulate da'wah fardiyahtoward new married couple to realize sakinah family. While the purpose of this research is to make the formulation of da'wah fardiyahtoward new married couple to realize sakinah family. The primary and secondary data sources were taken from books related toda’wah Islamic as well as some commentary, communication science and magazine. The results of research in-depth study of various sources showed that the effort to realize the family into sakinah family based on Islamic values is one of responsibilities of Muslims and he who has competence in their field. People who have competence in the field is proselytizer and the element that has the authority is government. The government as an extension to Ministry of Religious Affairs in which there are religious counselors. Therefore da'i in the spiritual field and the government can support of funds. The formulation of da'wah fardiyah against newly married husband and wife to realize sakinah family that is some stage that is stage, preparation consist of preparation of proselytizer and preparation of target and program. Then the implementation stage is consisting of introduction, approach and delivery of materials, program evaluation, program maturation and establishment of cadres of proselytizer.